2019
DOI: 10.1136/bcr-2019-231830
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium bovisprosthetic joint infection following intravesical instillation of BCG for bladder cancer

Abstract: A 91-year-old man with a history of intravesicular BCG therapy for recurrent bladder cancer and bilateral total hip arthroplasty (THA) presented with left hip pain. He was noted to have a fluid collection over the left lateral hip and hip X-ray showed loosening of the prosthetic hip stem indicative of a prosthetic joint infection (PJI). He subsequently underwent removal of the THA and insertion of an antibiotic spacer. He was discharged on intravenous ceftriaxone for presumed culture negative PJI. Intraoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In literature, there is a variation in treatment duration ranging from six months to two years; only one case was treated during four months (ICD). The rationale for this variation is not quite clear but might depend on clinical recovery of the individual patients and/or negative culture [15,20,21,22]. For the four patients in whom the implant was not removed, antibiotic treatment lasted at least 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, there is a variation in treatment duration ranging from six months to two years; only one case was treated during four months (ICD). The rationale for this variation is not quite clear but might depend on clinical recovery of the individual patients and/or negative culture [15,20,21,22]. For the four patients in whom the implant was not removed, antibiotic treatment lasted at least 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated BCG infections of prosthetic joints are distinctly rare. A review of Google Scholar and PubMed reveals that approximately 14 cases have been reported in the literature, including the current case [9][10][11][12][13][14][15][16][17]. Joints involved were predominantly hips (10 cases), total knee arthroplasty (3 cases), and one case of shoulder prosthetic joint infection [16] are reported.…”
Section: Discussionmentioning
confidence: 99%
“…Herein we present a case of a challenging workup, diagnosis, and treatment of a PJI due to Bacillus Calmette-Guérin (BCG), administered 3 years prior to TKA in the treatment of bladder cancer. A prior report has described a case of BCG, employed in the treatment of nonmuscle-invasive bladder cancer, which disseminated and led to PJI [ 11 ], though this has not been otherwise frequently described in the arthroplasty literature. The clinical course, diagnostic, and treatment challenges in this case will inform surgeons and clinicians of this rare PJI etiology.…”
Section: Introductionmentioning
confidence: 99%